(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Skin aging, driven by intrinsic and extrinsic factors, necessitates advanced delivery systems for effective therapeutic compound delivery. This study developed and characterized solid lipid nanoparticles loaded with hydroalcoholic extracts of Vitis vinifera L. (grape seed), Ferula assa-foetida L. (gum resin), and Rosa sinensis L. (flowers) for targeted skin anti-aging therapy. Extracts were prepared and then encapsulated into SLNs using high-shear homogenization followed by ultrasonication. Physicochemical characterization revealed nano-sized particles (average diameter < 200 nm), narrow polydispersity indices (0.15-0.24), negative zeta potentials (-24.8 to -29.2 mV), and high entrapment efficiencies (>79%). Transmission Electron Microscopy confirmed spherical morphology without aggregation. In vitro release studies demonstrated sustained release of active compounds over 24 hours from SLN formulations, contrasting with burst release from free extracts. Skin permeation studies using Strat-M® membranes showed significantly enhanced permeation and deposition of marker compounds, with mixed extract SLNs yielding the highest values i.e. 35.2 ± 2.8 μg/cm2 for resveratrol from MIX-SLN vs. 12.4 ± 1.1 μg/cm2 for free V. vinifera L. Biological assays in human dermal fibroblasts demonstrated the non-cytotoxic nature of SLNs. MIX-SLN reduced intracellular ROS by 62%, downregulated MMP-1 by 55%, upregulated collagen I by 48%, and decreased SA-β-gal positive cells by 70%. All data were found significant at *p < 0.05, **p < 0.01 vs. control/untreated. Furthermore, elevated antioxidant enzymes, and inhibited pro-inflammatory cytokines (TNF-α and IL-6) by 68% and 72%, respectively. These findings confirm the potential of SLNs as a novel and effective delivery system for plant-derived bioactive compounds, offering enhanced permeation, sustained release, and potent anti-aging, antioxidant, and anti-inflammatory activities, thereby improving the therapeutic efficacy of natural extracts for dermal applications.